2003
DOI: 10.1002/polb.10657
|View full text |Cite
|
Sign up to set email alerts
|

High‐efficiency doped polymeric organic light‐emitting diodes

Abstract: Fabrication of polymer light‐emitting diodes based on emission from the phosphorescent molecule fac‐tris(2‐phenylpyridine) iridium doped into a poly(N‐vinyl carbazole) host are reported. For single‐layered devices with magnesium‐silver cathodes, the luminance efficiency at 20 mA/cm2 was measured as 8.7 cd/A. This efficiency could be increased by over a factor of two by incorporation of evaporated small‐molecule layers into the device structure. Significant increases in device efficiency were also obtained with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…[16] A significant improvement was achieved by using CsF/Al or Cs/Al as the cathode. [15][16][17][18] It was further possible to improve hole injection from the polymeric PEDOT:PSS [poly (3,4-ethylenedioxythiophene) doped with poly(styrene sulfonate)] anode by adding the well-known hole-transporting molecule N,N′-diphenyl-N,N′-(bis (3-methylphenyl)- [1,1-biphenyl]-4,4′-diamine (TPD) to the PVK-based emission layer. [18] Electrophosphorescent devices with an optimized layer composition exhibited a maximum external quantum efficiency (EQE) of 10.7 %.…”
mentioning
confidence: 99%
“…[16] A significant improvement was achieved by using CsF/Al or Cs/Al as the cathode. [15][16][17][18] It was further possible to improve hole injection from the polymeric PEDOT:PSS [poly (3,4-ethylenedioxythiophene) doped with poly(styrene sulfonate)] anode by adding the well-known hole-transporting molecule N,N′-diphenyl-N,N′-(bis (3-methylphenyl)- [1,1-biphenyl]-4,4′-diamine (TPD) to the PVK-based emission layer. [18] Electrophosphorescent devices with an optimized layer composition exhibited a maximum external quantum efficiency (EQE) of 10.7 %.…”
mentioning
confidence: 99%
“…For pLEDs, phosphorescent emitters have also been used, but these devices show poor electrical properties (eg. high turn-on voltage), particularly when using high-energy phosphorescent emitters [11,15]. The reason for this is that to be able to use high-energy phosphorescent emitters, the host polymer should have a triplet excited state with a higher energy than that of the emitter to prevent the polymer host from quenching the emission.…”
Section: Theorymentioning
confidence: 99%
“…MgAg is a classical example of electron contact for most organic materials [3]. K. M. Vaeth et al reported highly efficient injection cathodes by inserting thin lithium fluoride (LiF) or cesium fluoride (CsF) between organic layer and cathode metals [4]. In the case of the devices with LiF contained cathodes, there are some reports about mechanisms that proposed for enhanced electron injection, including tunneling effect [5], band bending at the interface between organic layer and metal layer [6], lowering the work function of metal [7], formation of dipoles at the interface between organic layer and metal layer [8], and LiF dissociation with Li atoms and subsequent and generate organic anions [9].…”
Section: Introductionmentioning
confidence: 99%